Pediatric Obstructive Sleep Apnea and the Critical Role of Oral-Facial Growth: Evidences - Guilleminault, Christian; Huang, Yu shu (Frontiers in Neurology, 2013)
Aims: Review of evidence in support of an oral-facial growth impairment in the development of pediatric sleep apnea in non-obese children Method: Review of experimental data from infant monkeys with experimentally induced nasal resistance. Review of early historical data in the orthodontic literature indicating the abnormal oral-facial development associated with mouth breathing and nasal resistance. Review of the progressive demonstration of sleep disordered breathing in children who underwent incomplete treatment of OSA with adenotonsillectomy, and demonstration of abnormal oral-facial anatomy that must often to be treated in order for the resolution of OSA. Review of long term recurrence data on OSA and indication of oral-facial myofunctional dysfunction in association with the recurrence of OSA. Results: Presentation of prospective data on premature infants and sleep-disordered-breathing (SDB)-treated children, supporting the concept of oral-facial hypotonia. Presentation of evidence supporting hypotonia as a primary element in the development of oral-facial anatomic abnormalities leading to abnormal breathing during sleep. Continuous interaction between oral facial muscle tone, maxillary-mandibular growth and development of SDB. Role of myofunctional re-education with orthodontics and elimination of upper airway soft tissue in the treatment of non-obese SDB children. Conclusion: Pediatric OSA in non-obese children is a disorder of oral facial growth.